2005
DOI: 10.1111/j.1600-0447.2004.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Newer antipsychotic drugs and obesity in children and adolescents. How should we assess drug‐associated weight gain?

Abstract: Weight gain may be a major problem when prescribing newer antipsychotic drugs in the pediatric population. Risperidone is associated with less weight gain than olanzapine. Published reports and studies have not utilized state-of-the-art techniques using BMI with readily available growth charts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
1
18
0
5
Order By: Relevance
“…BMI differences found between groups, and their association with cumulative SGA dose, but not with FGA, were significant and consistent with previously published data (Stigler et al 2004;Vieweg et al 2005). BMI correlated with increased appetite, which is one of the main mechanisms involved in weight gain, via drug affinity for histaminergic and alpha-1-adrenergic receptors (Baptista et al 2004).…”
Section: Antipsychotics Side Effects 497supporting
confidence: 90%
See 1 more Smart Citation
“…BMI differences found between groups, and their association with cumulative SGA dose, but not with FGA, were significant and consistent with previously published data (Stigler et al 2004;Vieweg et al 2005). BMI correlated with increased appetite, which is one of the main mechanisms involved in weight gain, via drug affinity for histaminergic and alpha-1-adrenergic receptors (Baptista et al 2004).…”
Section: Antipsychotics Side Effects 497supporting
confidence: 90%
“…Increased prolactin serum levels, often seen with FGAs, have also been described in pediatric populations with the newer drugs, and their possible long-term repercussions on bone density and sexual function remain uncertain (Wudarsky et al 1999;Findling et al 2003;Pappagallo and Silva 2004). The same applies to weight gain (Baptista et al 2004;Stigler et al 2004;Vieweg et al 2005) and hyperglycemia (Lindenmayer et al 2001). Dyslipidemia, including hypercholesterolemia and hypertriglyceridemia, has been described in association with SGA treatment, as well as with schizophrenic disorders (Huang and Cheng 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, BMI Á the most appropriate approach to tracking changes in weight among paediatric patients Á was not routinely used by respondents to monitor weight gain as less than half of respondents reported measuring height (47% at initial assessment and 50% regularly thereafter). 63 Finally, waist circumference was measured by 24% of respondents initially and 28% thereafter to track weight gain. Previous studies have reported that waist circumference is not commonly measured by clinicians in adults, 59,60 even though it is a non-invasive way to monitor central adiposity, a recognized component of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Los valores umbral son diferentes de los utilizados en los adultos 20,23,24 . No hay una definición generalmente aceptada del aumento de peso que es clínicamente significativo durante el desarrollo, pero se ha propuesto y aplicado como definición el aumento del IMC de al menos 0,5 puntuaciones z (es decir, desviaciones estándar 20 ) 128 .…”
Section: Peso Corporalunclassified
“…Existen tablas de valores normales según el sexo y la edad 20,128 . En los niños y adolescentes que se encuentran por encima del percentil 85 y no alcanzan el percentil 95 para el IMC según su edad y sexo, se considera que hay un «sobrepeso», mientras que el IMC situado en el percentil 95 para la edad y sexo o por encima de él se considera indicativo de «obesidad» (http://www.cdc.gov/obesity/defining.html) 20,24,128 .…”
Section: Peso Corporalunclassified